Salidroside alleviates high glucose-induced oxidative stress and extracellular matrix accumulation in rat glomerular mesangial cells by the TXNIP-NLRP3 inflammasome pathway. (25th December 2017) - Wang, Shiying; Zhao, Xinxin; Yang, Suxia; Chen, Baoping; Shi, Jun
Abstract: Diabetic nephropathy (DN) is a metabolic disease characterized by mesangial cell proliferation and extracellular matrix (ECM) accumulation. Salidroside (SAL) is the major ingredient in Rhodiola rosea and possesses beneficial effects on DN. This study aimed to evaluate the effect of SAL on high glucose (HG)-induced oxidative stress and ECM accumulation and the underlying mechanism. Rat glomerular mesangial cells HBZY-1 were induced by high glucose (HG) in the presence or absence of SAL. Cell proliferation was measured by CCK-8 assay. The reactive oxygen species (ROS) level, malondialdehyde (MDA) level and superoxide dismutase (SOD) activity were detected to evaluate oxidative stress. The expression levels of ECM proteins including fibronectin (FN) and type IV collagen (Coll IV) were detected by qRT-PCR and western blot analysis. The expressions of thioredoxin-interacting protein (TXNIP), nod-like receptor protein 3 (NLRP3), apoptosis-associated speck-like protein containing CARD (ASC), and caspase-1 were assessed by western blot. Si-TXNIP or si-NC was transfected into HBZY-1 cells to inhibit TXNIP-NLRP3 inflammasome pathway. The results showed that SAL treatment alleviated HG-induced cell proliferation. SAL reduced the levels of ROS and MDA, and induced the SOD activity. Besides, the mRNA and protein expressions of FN and Coll IV were decreased by SAL. The expression levels of TXNIP, NLRP3, ASC, and caspase-1 were reduced in the SAL treated cells. In addition, TXNIP knockdown inhibited TXNIP-NLRP3 inflammasome activation and suppressed HG-induced cell proliferation, oxidative stress, and ECM accumulation. In conclusion, SAL alleviated HG-induced oxidative stress and ECM accumulation in rat glomerular mesangial cells by the TXNIP-NLRP3 inflammasome pathway. Highlights: SAL inhibits HG-induced cell proliferation in HBZY-1 cells. SAL alleviates HG-induced oxidative stress. SAL reduces HG-induced ECM accumulation. SAL inhibits HG-induced TXNIP-NLRP3 inflammasome activation.